Faktor-faktor yang berpengaruh terhadap penyerapan anggaran dengan komitmen organisasi sebagai variabel moderasi - Sososutiksno, Christina (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this research is to examine the influence of Budget Planning, Budget Execution, and Human Resource Competence on Budget Absorption with Organizational Commitment as a Moderating Variable. The sample used in this research is an employee who handles budget management, amounting to 40 respondents. This type of research is quantitative research, namely by distributing questionnaires to respondents. The data analysis carried out proves that Budget Planning and Human Resource Competence have a positive and significant effect on Budget Absorption but if Budget Execution does not affect budget absorption then organizational commitment does not moderate Budget Planning, Budget Execution, and Human Resource Competence on Budget Absorption.